2021
DOI: 10.1039/d1dt01198g
|View full text |Cite
|
Sign up to set email alerts
|

Novel primary phosphinecarboxamides derived from diamines

Abstract: We describe the synthesis of N-functionalized phosphinecarboxamides obtained by reaction of the 2-phosphaethynolate anion (PCO–) with diamines, specifically hydrazine, methylenediamine and ethylenediamine. The resulting neutral compounds can be deprotonated to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…65,66 Goicoechea et al synthesised novel N -functionalised phosphinecarboxamides by the reaction of the OCP − anion with diamines, in the presence of acid. 67 In 2020, Goicoechea and Štěpnička et al reported the synthesis of ferrocenyl-substituted phosphinecarboxamides, FcNHC(O)PH 2 ( 68 ; Fc = ferrocenyl) and FcCH 2 NHC(O)PH 2 ( 69 ) with terminal PH 2 groups by the reaction of [Na(dioxane) x ](OCP) with aminoferrocene and (ferrocenylmethyl)ammonium chloride, respectively (Schemes 23 and 24). 68 The 31 P NMR of these phosphaureas showed resonance at δ = −129.8 ( 68 ) and −132.8 ( 69 ) ppm, corresponding to PH 2 groups.…”
Section: Reactivity Of Ocp− Towards Main-group Elementsmentioning
confidence: 99%
“…65,66 Goicoechea et al synthesised novel N -functionalised phosphinecarboxamides by the reaction of the OCP − anion with diamines, in the presence of acid. 67 In 2020, Goicoechea and Štěpnička et al reported the synthesis of ferrocenyl-substituted phosphinecarboxamides, FcNHC(O)PH 2 ( 68 ; Fc = ferrocenyl) and FcCH 2 NHC(O)PH 2 ( 69 ) with terminal PH 2 groups by the reaction of [Na(dioxane) x ](OCP) with aminoferrocene and (ferrocenylmethyl)ammonium chloride, respectively (Schemes 23 and 24). 68 The 31 P NMR of these phosphaureas showed resonance at δ = −129.8 ( 68 ) and −132.8 ( 69 ) ppm, corresponding to PH 2 groups.…”
Section: Reactivity Of Ocp− Towards Main-group Elementsmentioning
confidence: 99%